Follow‐Up of Alcohol Consumption After Liver Transplantation: Interest of an Addiction Team?. (9th December 2016) - Donnadieu‐Rigole, Hélène; Olive, Laetitia; Nalpas, Bertrand; Winter, Audrey; Ursic‐Bedoya, José; Faure, Stéphanie; Pageaux, Georges‐Philippe; Perney, Pascal
Abstract : Background: Alcohol relapses after liver transplantation (LT) constitute a critical issue. Because there is no widely accepted definition of LT, its prevalence varies from 7 to 95% across studies. Only a severe relapse, the frequency of which is estimated to be 11 to 26%, decreases life expectancy after 5 years of LT and requires specific care. To improve the early identification of alcohol consumption among transplanted patients, liver transplant teams may be helped by input from an addiction team. Nevertheless, added benefit of involvement by addiction specialists in treating posttransplant patients has not been demonstrated. Thus, the aim of this study was to compare the evaluation of the alcohol consumption after LT performed routinely during the transplant consultation or obtained from a specific addiction consultation. Methods: This was a prospective single‐site study. Patients were seen consecutively by their hepatologist and by an addiction specialist, and they completed the Alcohol Use Disorders Identification Test–Consumption (AUDIT‐C). Thus, the patient's alcohol status was assessed using 3 different sources of information: the hepatologist's interview, the AUDIT‐C score, and the addiction specialist visit. Results: One hundred forty‐one patients were consecutively evaluated. Alcohol consumption was identified by the hepatologist in 31 patients (21.9%), in 52 (36.8%) using the AUDIT‐C questionnaire, and in 58 (41.1%) by the addiction specialist. The 31 patients concerned reported an average of 6.5 alcohol units/wk to the transplant physician, a number which was significantly greater ( p  = 0.001) by 8.6 units/wk when they were interviewed by the addiction specialist. Conclusions: This study highlights the clinical utility of a systematic addiction consultation among liver transplant patients, irrespective of the reason for transplantation. Abstract : Alcohol relapses after liver transplantation constitutes a critical issue. The aim of the study was to compare the evaluation of the alcohol consumption after LT using three different sources: the hepatologist interview, the AUDIT, and the addiction specialist visit. Alcohol consumption was identified in 31 of 141 patients by the hepatologist, in 52 using the AUDIT, and in 58 by the addiction specialist. This study highlights the interest of a systematic addiction consultation among liver transplant patients.